Legal Analysis of the Protection of National Health Insurance Participants in Indonesia - Atmawijaya, Surya; Saliman, Abdul Rasyid; Agustina, Enny (International Journal of Science and Society, 2025)
The National Health Insurance (JKN) is a program to provide equitable access to healthcare services for all citizens of Indonesia and also to improve the quality of health services received by the community However, various challenges and obstacles in the implementation of this program persist. This study aims to analyze the legal protection of health insurance carried out by BPJS Kesehatan. The type of research used by the authors in this study is normative legal research. This legal research examines relevant legislation, regulations, and legal principles governing JKN, alongside case studies that highlight practical issues faced by participants. This study recommends enhancing oversight mechanisms and evaluation processes concerning JKN implementation, as well as improving educational initiatives for participants regarding their rights and obligations.